2018
DOI: 10.1002/cmdc.201800177
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of 1‐Aryl‐5,6‐dihydropyrrolo[2,1‐a]isoquinoline Derivatives as Reversers of P‐Glycoprotein‐Mediated Multidrug Resistance in Tumor Cells

Abstract: A number of aza-heterocyclic compounds, which share the 5,6-dihydropyrrolo[2,1-a]isoquinoline (DHPIQ) scaffold with members of the lamellarin alkaloid family, were synthesized and evaluated for their ability to reverse in vitro multidrug resistance in cancer cells through inhibition of P-glycoprotein (P-gp) and/or multidrug-resistance-associated protein 1. Most of the investigated DHPIQ compounds proved to be selective P-gp modulators, and the most potent modulator, 8,9-diethoxy-1-(3,4-diethoxyphenyl)-3-(furan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…SAR studies emphasized lipophilicity's role in increasing compounds' biological potency. 88 Novel Schiff compounds based on the pyrrolo[2,1- a ]isoquinoline skeleton 192 , 193 were synthesized and the cytotoxicity was tested against RD (rhabdomyosarcoma), HCT116 (intestinal carcinoma), HeLa (adenocarcinoma of the cervix uterus), and A549 (lung adenocarcinoma) cell lines, some of the synthesized compounds were non-cytotoxic in the low micromolar range (<30 μM). Moreover, it could be noticed that (i) pyrrolo[2,1- a ]isoquinoline' Schiff bases were mostly less cytotoxic than the parent aldehydes, (ii) the adducts bearing a phenyl ring at C-3 were generally less cytotoxic than the corresponding unsubstituted compounds, and (iii) homobivalent Schiff base derivatives were significantly less cytotoxic than the corresponding mono Schiff bases.…”
Section: Approach To the Synthesis And Diversification Of Isoquinolin...mentioning
confidence: 99%
“…SAR studies emphasized lipophilicity's role in increasing compounds' biological potency. 88 Novel Schiff compounds based on the pyrrolo[2,1- a ]isoquinoline skeleton 192 , 193 were synthesized and the cytotoxicity was tested against RD (rhabdomyosarcoma), HCT116 (intestinal carcinoma), HeLa (adenocarcinoma of the cervix uterus), and A549 (lung adenocarcinoma) cell lines, some of the synthesized compounds were non-cytotoxic in the low micromolar range (<30 μM). Moreover, it could be noticed that (i) pyrrolo[2,1- a ]isoquinoline' Schiff bases were mostly less cytotoxic than the parent aldehydes, (ii) the adducts bearing a phenyl ring at C-3 were generally less cytotoxic than the corresponding unsubstituted compounds, and (iii) homobivalent Schiff base derivatives were significantly less cytotoxic than the corresponding mono Schiff bases.…”
Section: Approach To the Synthesis And Diversification Of Isoquinolin...mentioning
confidence: 99%
“…constructions of pyrrolo[2,1-a]isoquinoline derivatives through aza-Michael addition-initiated cascade reactions with dihydroisoquinoline and nitroolefin have been achieved by the groups of Ruchirawat, Sosnovskikh and Altomare. 5,8 Elegant methodologies on pyrrolo[2,1a]isoquinoline preparation with nitroolefins via the in situ oxidation of tetrahydroisoquinoline ester have been developed by Xiao, Lu Hosseini-Sarvari, Wang, Xie/Li and Wang/Zhen. 7,9 Nyerges and coworkers have established a convenient stepwise synthesis of NO2-bearing pyrroloisoquinolines with dihydroisoquinolines, activated bromides and nitroolefins as starting material.…”
Section: Efficientmentioning
confidence: 99%
“…The 6,7-dimethoxylated tetrahydroisoquinoline scaffold was the important pharmacophore that was nearly Apart from the tariquidar analogs, a series of tetrahydroisoquinoline-based P-gp inhibitors, with relatively simplified structures, have been reported 57,60,61,[84][85][86][87][88][89] and the general structure was characterized by connecting the important pharmacophore 6,7-dimethoxy-tetrahydroisoquinoline to an aromatic moiety by a flexible linker ( Figure 4A). After determining the P-gp inhibitory efficacy of these compounds in vitro, the general SAR studies of these compounds ( Figure 4A) indicated that the aromatic moiety is flexible and appropriate substitution on the aromatic ring could increase the efficacy.…”
Section: Compounds With a Tetrahydroisoquinoline Scaffoldmentioning
confidence: 99%